2020
DOI: 10.5694/mja2.50524
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy naloxone supply, before and after rescheduling as an over‐the‐counter drug: sales and prescriptions data, 2014–2018

Abstract: Objectives: To characterise the community pharmacy supply of naloxone by supply type -individual prescription, prescriber bag, and non-dispensed (supplied over the counter or expired) -during 2014-2018; to examine whether the 2016 rescheduling of naloxone as an over-the-counter drug influenced non-dispensed naloxone supply volume.Design, setting: Analysis of monthly naloxone prescriptions (Pharmaceutical Benefits Scheme) and sales data (IQVIA), 2014-2018, for Australia and by state and territory; time series a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In their study published in this issue of the MJA , Tse and colleagues assessed naloxone supply to community pharmacies in Australia during 2014–2018 by analysing Pharmaceutical Benefits Scheme (PBS) prescriptions data and sales data supplied by IQVIA . Their findings highlight challenges in expanding THN programs.…”
mentioning
confidence: 99%
“…In their study published in this issue of the MJA , Tse and colleagues assessed naloxone supply to community pharmacies in Australia during 2014–2018 by analysing Pharmaceutical Benefits Scheme (PBS) prescriptions data and sales data supplied by IQVIA . Their findings highlight challenges in expanding THN programs.…”
mentioning
confidence: 99%
“…Most naloxone was still being supplied as a PBS Prescriber Bag item rather than being obtained over-the-counter. 4 In early 2019, the Australian Government therefore funded a pilot program in New South Wales, South Australia and Western Australia to provide naloxone free of charge through participating pharmacies and other services to people at risk of opioid overdose, and their carers and friends. 5 The pilot has been extended until June 2021.…”
Section: Naloxone For Opioid Toxicity and Overdose In The Communitymentioning
confidence: 99%
“…Using these indications, an Australian study reported that 78% of patients on Schedule 8 opioids for chronic non‐cancer pain qualified for take‐home naloxone 8,9 . Yet current national data show that less than 3% of all naloxone supplied is on individual PBS prescriptions, with most naloxone prescriptions accounted for by harm reduction programs 10 . An additional negligible amount of naloxone is sold over the counter by pharmacists 10 .…”
mentioning
confidence: 99%
“…Yet current national data show that less than 3% of all naloxone supplied is on individual PBS prescriptions, with most naloxone prescriptions accounted for by harm reduction programs 10 . An additional negligible amount of naloxone is sold over the counter by pharmacists 10 . Between 2014 and 2018, an estimated 10 642 units of naloxone were supplied in Australia.…”
mentioning
confidence: 99%
See 1 more Smart Citation